ROLE OF DUAL-ENERGY COMPUTED TOMOGRAPHY IN THE EMERGENCY DIAGNOSIS OF KNEE BONE MARROW EDEMA: A COMPARATIVE STUDY WITH MAGNETIC RESONANCE IMAGING - GEETHANJALI SUNDARAM,; SEETHARAMAN CANNANE,; TAPAS KUMAR SAHU,; JEEVITHAN SHANMUGAM,; PANKAJ MEHTA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Key markers of injury processes in acute knee trauma are bone bruises, which are detected by magnetic resonance imaging (MRI) as increased signal intensity on T2-weighted images and signal loss on T1-weighted imaging. However, due to its restricted availability and lengthy acquisition times, particularly in emergency situations, MRI is not often employed in knee trauma cases. A viable substitute is dual-energy computed tomography (DECT) with virtual non-calcium (VNCa) techniques, which improves bone marrow edema (BME) visibility and allows for greater material distinction. This study uses MRI as the reference standard to assess the diagnostic performance of third-generation DECT and VNCa methods for detecting BME in acute knee injuries. Methods: This prospective observational study involved 40 patients with acute knee trauma who had both MRI and DECT between July 2019 and July 2021 at Kovai Medical Center and Hospital in Coimbatore. Individuals who were pregnant had a history of knee injuries or were above the age of 18 were eliminated, as were those who had an MRI or CT contraindication. Siemens Healthcare’s Somatom Force, a third-generation 192-slice dual-source CT scanner, was used for DECT imaging, while Philips Ingenia 1.5T was used for MRI. Image analysis used SPSS version 27.0 for statistical analysis to determine whether BME was present in MRI and DECT images. Results: The study participants had a mean age of 47±16 years, predominantly male (72.5%). DECT demonstrated a sensitivity of 81.15% and a specificity of 96.70% for detecting BME compared to MRI. The diagnostic accuracy was notably high in the lateral femoral condyle (sensitivity and specificity of 93.33%) and the lateral tibial condyle (sensitivity and specificity of 86.36%). Overall, DECT identified 59 out of 69 MRI-positive regions, reflecting its robustness in detecting true positives and true negatives in acute trauma settings. Conclusion: Third-generation DECT with VNCa techniques is a highly effective imaging modality for detecting edema of the bone marrow in acute knee trauma, offering high diagnostic accuracy comparable to MRI. It is ability to provide clear visual differentiation and rapid acquisition makes it a valuable alternative, particularly in emergency settings where MRI is unavailable or contraindicated. DECT’s shorter reconstruction time and high reliability can optimize workflow and improve patient outcomes, underscoring its potential role in early diagnosis and management of knee trauma.